Oil jet with dispersant: Macro‐scale hydrodynamics and tip streaming. Issue 11 (18th July 2017) - Zhao, Lin; Gao, Feng; Boufadel, Michel C.; King, Thomas; Robinson, Brian; Lee, Kenneth; Conmy, Robyn
Abstract : Modeling the movement of oil released underwater is a challenging task due to limitations in measuring the hydrodynamics in an oil‐water system. In this work, we conducted an experiment of horizontal release of oil without and with dispersant. The model VDROP‐J was used and compared to the model JETLAG, a miscible plume trajectory model. Both models were found to reproduce the oil jet hydrodynamics for oil without and with dispersant. The predicted DSD from VDROP‐J matched closely observation for untreated oil. For oil with dispersant, experimental results have shown evidence that tip streaming occurred. For this purpose, a new conceptual module was developed in VDROP‐J to capture the tip streaming phenomenon and an excellent match was achieved with observation. This study is the first to report tip streaming occurring in underwater oil jets, which should have consequences on predicting the DSD when dispersant are used on an underwater oil release. © 2017 American Institute of Chemical Engineers AIChE J, 2017